PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Sri Donna Agustin; Nur Islami; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe the application of Think Talk Write Cooperative Type models in thermodynamic material. The study was conducted in eleventh grade of Senior High School 1 Rambatan West Sumatra. This type of research was quasi-experimental with the design of the Posttest Only Nonequivalent Control Group. The data collection technique was un understanding test using a score instrument. The data analysis technique was in the form of descriptive analysis and inferential analysis. The results obtained by the average score of concept understanding in the experimental class was 80.75 with good categories, while in the control class it was 47.99 in the poor category. Based on the analysis of T-test data was obtained 9,027>1,6575 and 0,00<0,05 so that H0 was rejected. The conclusions of this study are: the application of Think Talk Write type Cooperative learning models is more effective in improving students 'conceptual understanding and there are significant differences in students' conceptual understanding between the experimental class and the control class.Keywords : Cooperative type Think Talk Write, concepts understanding, Laws of Thermodynamics